Cross-Border Integration: Case of the Russian Far East and North-East of China - Markova,Valeria (2014)
Cooperation initiatives across national borders is growing phenomenon all over the world due to developing globalization and regionalization. Growing trend of spatial reorganization of production process, massive growth of markets and labor recourses, opportunities to “escape” from spatial and resource dependencies are stimulating international cross-border interactions and emergence of cross-border areas. This research paper highlights the case of the Russian Far East and the North-East of China region that has potential to develop into effective cross-border area. The analysis is following an extensive literature review both on theoretical and empirical evidences on cross-border areas, their characteristics, integration barriers and incentives and policy intervention methods. Main emphasis is done on the most recent policy on regional cooperation between the Russian Far East and the North East of China for the period 2009- 2018. The study showed that cross-border cooperation is appropriate development path for this area and proposed in the policy initiatives correspond to initial integration stage characteristics. Despite inability to predict the future character of cross-border interactions in this area, due to early stage of integration relations, policy document indicated attempts to test innovation capacity of forming region.
Keywords: cross-border area; integration process; proximities; integration policy